2020
DOI: 10.17083/ijsg.v5i3.240
|View full text |Cite
|
Sign up to set email alerts
|

Visuospatial Abilities Training with Digital Games in a Primary School

Abstract: The “A me gli occhi” project was organized to support the development and consolidation of visuospatial abilities in students of the last two years of the Italian primary school, with the hypothesis that such a training would have a positive impact on their performance in mathematics. Twenty game based training sessions were set up along the whole school year, involving two experimental classes, while another two classes served as control group. Students’ mathematical abilities were measured at the beginning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…, other studies show statistically significant improvements with the use of STEM games in schools (e.g. Freina et al, 2018).…”
Section: Stem Learning With Gamificationmentioning
confidence: 91%
“…, other studies show statistically significant improvements with the use of STEM games in schools (e.g. Freina et al, 2018).…”
Section: Stem Learning With Gamificationmentioning
confidence: 91%
“…For example, origami/paper folding, the number board game, counters, Cuisenaire rods, Unifix cubes, paper money, pattern blocks, base-10 blocks etc., are often used in the math classroom. A recent study by Freina et al (2018) found that digital games supported the development and consolidation of visuospatial abilities in students of the last 2 years of the primary school, and such a training would have a positive impact on their mathematics performance. Similar results were obtained by Otten et al (2020) .…”
Section: Introductionmentioning
confidence: 99%
“…Initially, some studies were focused on the development of logical reasoning [22,23]. Later, a project was organized aiming to foster primary school students' visuospatial abilities and assessing the impact of such a training on their performance in mathematics [24]. During the development of these projects, even though students enjoyed playing with most of the selected games, they showed a deeper commitment when they could be more creative and active.…”
Section: Introductionmentioning
confidence: 99%
“…During the development of these projects, even though students enjoyed playing with most of the selected games, they showed a deeper commitment when they could be more creative and active. For example, creating virtual houses in Minecraft (a sandbox digital game where players can build objects with a variety of different blocks in a 3D virtual world) was particularly appreciated by nearly all the students [24]. Starting from this observation, and from results of previous research projects on collaborative programming with tangibles in primary schools [25], a new project was started.…”
Section: Introductionmentioning
confidence: 99%